2014
DOI: 10.1515/reveh-2014-0063
|View full text |Cite
|
Sign up to set email alerts
|

Toenail as a biomarker of heavy metal exposure via drinking water: a systematic review

Abstract: AbstractToenail is metabolic end product of the skin, which can provide information about heavy metal accumulation in human cells. Slow growth rates of toenail can represent heavy metal exposure from 2 to 12 months before the clipping. The toenail is a non-invasive biomarker that is easy to collect and store and is stable over time. In this systematic review, the suitability of toenail as a long-term biomarker was reviewed, along with the analysis and validation of toenail and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
9
0
4
Order By: Relevance
“…57 Parents were asked to collect their own and their children's toenail clippings from all toes and mail back the samples in provided envelopes. Average time from birth to collection was 2.8 months (range 0.3-7.1 months).…”
Section: Metals Exposurementioning
confidence: 99%
“…57 Parents were asked to collect their own and their children's toenail clippings from all toes and mail back the samples in provided envelopes. Average time from birth to collection was 2.8 months (range 0.3-7.1 months).…”
Section: Metals Exposurementioning
confidence: 99%
“…For example, in the colon cancer study measuring trace element accumulation in toenails [2], we observed a statistically significant association between the exposure level and DL in Appalachian cancer cases for at least six trace elements (Table IV). This may be because trace elements can cause adverse effects on metabolism and therefore lead to slow growth rate of toenails [3]. As a result, toenail samples obtained from individuals with high exposure to trace elements tend to have low masses and thus high DLs.…”
Section: Introductionmentioning
confidence: 99%
“…Ambos os elementos são persistentes no ambiente (REHMAN et al 2017), sendo que a exposição ambiental a esses elementos pode se dar por diversas vias, em especial por inalação, ingestão e até mesmo contato dérmico. Seus níveis podem ser analisados por meio de coletas de amostras oriundas de matrizes ambientais (água, solo e ar), de alimentos, bem como em amostras biológicas (sangue, urina, unha, cabelo, entre outros) que, uma vez somadas, têm o potencial de fornecer dados mais completos da exposição humana (AB RAZAK et al, 2015a).…”
Section: Siglas Utilizadasunclassified
“…Sabe-se que tanto o chumbo quanto o cádmio podem ser tóxicos, mesmo que haja exposição em pequenas doses (KARRI et al, 2016;KIRA et al, 2016;SOARES et al, 2017;OLYMPIO et al, 2017). Ambos são mutagênicos e possuem um potencial de alterar o DNA das células, bem como atuar como disruptores endócrinos, acarretando em distúrbios no desenvolvimento (JIN et al, 2003;HENSON e CHEDRESE, 2004;IAVICOLI et al, 2009;AB RAZAK et al, 2015a;BURM et al, 2016;ATSDR, 2017b;ATSDR, 2019). Por exemplo, em relação às alterações genéticas, alguns estudos associaram o autismo em crianças com mutações no DNA, ocasionadas por exposições ambientais a EPT (WINDHAM et al, 2006;SEBAT et al, 2007;SMITH et al, 2009;KINNEY et al, 2010).…”
Section: Potencialmente Tóxicosunclassified
See 1 more Smart Citation